(untitled) (Iris Journal of Scholarship, 2019)
For many the term networking is cringe worthy. They picture awkward networking events, fake smiles, and sweaty handshakes. But is there another way? Can we network without feeling uncomfortable and like we are simply using people? Networking with the intent to build social capital is a viable alternative to traditional networking and presents networkers with comfort and peace of mind. In this paper we explore what social capital is and how it differs from networking. We discuss the importance of social capital and its components. Finally, we explore how one can build social capital through networking and introduce practical steps that can assist any individual to improve their networking. Ultimately, this paper will help individuals & organizations network more comfortably, efficiently and successfully.